Clinical and genetic heterogeneity in nemaline myopathy--a disease of skeletal muscle thin filaments - Sanoudou, D.; Beggs, A. H. (Trends Mol MedTrends Mol MedTrends Mol Med, 2001)
The term nemaline myopathy (NM) encompasses a heterogeneous group of disorders of primary skeletal muscle weakness characterized by the presence of nemaline rods in muscles of affected individuals. Disease severity is variable and unpredictable, with prognosis ranging from neonatal death to almost normal motor function. Recent advances in the identification of NM disease genes demonstrate that NM is a disease of the skeletal muscle sarcomere and, in particular, of the thin filaments. These findings are starting to alter the approach that neurologists and geneticists take to diagnosing and counseling patients with NM, and could lead to insights into specific directed therapies in the future.
Keywords: *Genetic Heterogeneity; Humans; Muscle, Skeletal/cytology/*pathology/ultrastructure; Myopathies, Nemaline/diagnosis/*genetics/*pathology/physiopathology; Sarcomeres/pathology/ultrastructure